1998
DOI: 10.1074/jbc.273.12.6710
|View full text |Cite
|
Sign up to set email alerts
|

The Thylakoid Lumen of Chloroplasts

Abstract: The chloroplast compartment enclosed by the thylakoid membrane, the "lumen," is poorly characterized. The major aims of this work were to design a procedure for the isolation of the thylakoid lumen which could be generally used to characterize lumenal proteins. The preparation was a stepwise procedure in which thylakoid membranes were isolated from intact chloroplasts. Loosely associated thylakoid surface proteins were removed, and following Yeda press fragmentation the lumenal content was recovered in the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…A BLAST search [23] revealed that the ¢rst peptide (Fig. 3A) corresponded to the 20 amino acid peptide (SwissProt accession number P82536) obtained earlier by N-terminal sequencing of the 'thylakoid lumenal 18 kDa protein' from spinach [3]. This can be considered independent con¢rmation of the localization of TLP20 in the thylakoid lumen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A BLAST search [23] revealed that the ¢rst peptide (Fig. 3A) corresponded to the 20 amino acid peptide (SwissProt accession number P82536) obtained earlier by N-terminal sequencing of the 'thylakoid lumenal 18 kDa protein' from spinach [3]. This can be considered independent con¢rmation of the localization of TLP20 in the thylakoid lumen.…”
Section: Resultsmentioning
confidence: 99%
“…The lumenal proteins were obtained from spinach thylakoids by the method of Kieselbach et al [3], which involves extensive washing of the thylakoids before disruption of the membranes by Yeda press. No PPIase activity was detected in the washed thylakoids before membrane disruption and the activity appeared only when soluble proteins were released from the lumen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these questions concerns the presence of nucleotides in such a potentially multifunctional cellular compartment as particularly suggested by indications for luminal chaperones (3,9) and ATP binding to luminal proteins (11). On the other hand, luminal preparations have been tested for presence of ATP and ATPase activity without any conclusive results (12), and none of the proteins identified through proteomics have shown to have any conventional nucleotide-binding motifs (10). Furthermore, transport of nucleotides across the thylakoid membrane has not been considered, in contrast to mitochondrial membranes, where an ATP͞ADP carrier (AAC) has been extensively studied (13,14).…”
mentioning
confidence: 99%